Analisis Makna dan Fungsi Onomatope dalam Webtoon “7 Wonders” Karya Metalu pada Season 1 - Umniatul Fadhilah; Suwadi Suwadi; Sugianti Sugianti (BADAN PENERBIT STIEPARI PRESS, 2024)
As we know, comics are a work that emphasizes their visual value more and more utilizes a text that is used as sound imitations to describe an event or events so they can be conveyed to readers. Even though Webtoon has presented a feature specifically such as music or sound effects, but still requires a word form in the form of imitations sound to give a more real effect to readers. This research aims to describe form, meaning and function of onomatopoeia in the Webtoon comic 7 Wonders by Metalu. This research using qualitative descriptive methods with data collection techniques using listening, taking notes, and documentation. Data analysis uses a qualitative descriptive method consisting of data collection, classification of onomatopoeia, and interpretation of meaning and function. The research results show that in comics Webtoon 7 Wonders by Metalu in season 1, there are seven types of onomatopoeic forms which produce 284 data, namely: (1) 82 onomatopoeic forms of human voices, (2) onomatopoeic forms of animal voices as many as 7 data, (3) onomatopoeic forms of object sounds totaling 55 data, (4) onomatopoeic forms of natural sounds totaling 5 data, (5) onomatopoeic forms of sound naturalness totaling 17 data, (6) onomatopoeic forms of sound color totaling 10 data, and (7) onomatopoeic forms of sound abstraction totaling 108 data.